2000
DOI: 10.1597/1545-1569_2000_037_0281_csbcwa_2.3.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Children with and without Cleft Lip and Cleft Palate, Part 1: Cephalometric Analysis

Abstract: Objective This study was conducted to compare craniofacial relationships, position, and curvature of the cervical spine between children with cleft lip and cleft palate who had been operated on and children without clefts. Method This study was performed in 28 children with mixed dentition. They were divided into two groups. The study group included 14 children with unilateral operated cleft lip and cleft palate, ranging in age from 6 to 12 years, who clinically presented with a short upper lip, abnormal lip s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Zúñiga et al. (25) compared the curvature of the cervical spine in children with cleft lip and palate with children without clefts. They found that the cleft children had significantly increased extension of the head and also a forward position of the cervical spine.…”
Section: Discussionmentioning
confidence: 99%
“…Zúñiga et al. (25) compared the curvature of the cervical spine in children with cleft lip and palate with children without clefts. They found that the cleft children had significantly increased extension of the head and also a forward position of the cervical spine.…”
Section: Discussionmentioning
confidence: 99%
“…Boys are more affected than girls (3/2). The cause is believed to be a combination of various genetic factors and possibly external, "environmental", unknown factors [14]. In some families, the cases accumulate over several generations without a precise mode of hereditary transmission being detected.…”
Section: General Points On Cleft Lip and Palatementioning
confidence: 99%